Effect of pressure on the tertiary structure and dynamics of folded basic pancreatic trypsin inhibitor - Li, H (1999)
The on-line high-pressure cell NMR technique was used to study pressure-induced changes in the tertiary structure and dynamics of a globular protein, basic pancreatic trypsin inhibitor (BPTI). Practically all the proton signals of BPTI were observed with (1)H two-dimensional NMR spectroscopy at 750 MHz at variable pressure between 1 and 2000 bar. Chemical shifts, nuclear Overhauser effect (NOE), and line shapes were used to analyze conformational and dynamic changes of the protein as functions of pressure. Linear, reversible, but nonuniform pressure-induced chemical shift changes of practically all the C(alpha) protons and side chain protons showed that the entire secondary and tertiary structures are altered by pressure within the folded ensemble of BPTI. The high field shift tendency of most side chain proton signals and the increase in NOE intensities of some specific side chain protons indicated a site-specific compaction of the tertiary structure. Pressure dependence of ring flip rates was deduced from resonance line shapes of the slices of the two-dimensional NMR spectrum for ring proton signals of Tyr-35 and Phe-45. The rates of the flip-flop motions were considerably reduced at high pressure, from which activation volumes were determined to be 85 +/- 20 A(3) (or 51.2 ml/mol) and 46 +/- 9 A(3) (or 27.7 ml/mol) for Tyr-35 and Phe-45, respectively, at 57 degrees C. The present experiments confirm that pressure affects the entire secondary and tertiary structures of a globular protein with specific compaction of a core, leading to quite significant changes in slow internal dynamics of a globular protein.